MUTU SEBAGAI STRATEGI PEMASARAN JASA PENDIDIKAN: Studi di SMP N 2 Blora - Arim Irsyadulloh Albin Jaya (Jurnal Studi Islam dan Sosial, 2019)
In the globalization era which is very competitive, marketing education services is very important for the continued existence of educational organizations. Therefore, every educational institution should have a strategy in marketing educational services. At the moment, there are many schools that have low marketing and do not yet have a competitive strategy so there needs to be an awareness of thinking in choosing a strategy to run marketing education services. A good service marketing strategy can be done through the selection of effective and efficient marketing strategies. This research is intended to determine the role of quality as the most appropriate strategy in marketing education services in SMP N 2 Blora. This type of research is a qualitative research with a case study approach. The sources of research are: informants, the process of school activities, and school documents. Data collection techniques use interview, observation, and study documents. Data analysis technique used is flow analysis models. The results showed that quality has an effective strategic role in the marketing strategy of education services in SMP N 2 Blora. The quality refers is the quality of educational inputs, the quality of educational processes, and the quality of education outputs. The standard measure of quality achievement through fulfillment of 8 National Education Standards. To realize superior quality, efforts must be made to maintain it, which is through four management functions, a). education quality planning; b) organizing the quality of education; c) implementation of education quality; d) evaluation of the education quality. From some of the existing descriptions, one of the efforts that can be done by schools to run in order to always exist and be more advanced in marketing education services, the school must choose the most appropriate strategy. Recommendations from this study is quality can be used as an effective strategy in marketing education services in Public and Private Junior High School.